MODEL PEMBELAJARAN SEJARAH BERBASIS ISU-ISU KONTROVERSIAL UNTUK MENINGKATKAN BERPIKIR HISTORIS MAHASISWA (STUDI PADA MAHASISWA SEJARAH UNIV. MUHAMMADIYAH PURWOKERTO) - Septianingsih, Sumiyatun; Joebagio, Hermanu; S., Sariyatun (HISTORIKA, 2014)
The research and development aimed by students’ attitude and knowledge related to the skill of historical thinking is still low and lack of students’ awareness history, and specifically the aims of this research are to: (1) Describe and analyze the process of historical learning teaching in historical education department of UMP. (2) Develop the historical learning model based on controversial issues to improve students’ historical thinking, and (3) examine the effectiveness of the historical learning model based on the controversial issues to improve the historical thinking.This developing research was used the research method and development (R&D). Technique of collecting data was observation, documentary, interview, questionnaire, and assessment test of historical thinking. Techniques of analyzing data were attitude scale and achievement test using t-test such as experiment class and control class with SPSS.16 program. The location of the research is in historical education department of Muhammadiyah University of Purwokerto by using purposive sampling. The steps of the research included: introduction of the study, developing the historical learning model and testing the effectiveness of the learning model was developed. The result of research showed that the historical learning model based on the controversial issues was developed to be able to improve the historical thinking skill, was showed by the result of measuring test of pre-test, post-test, LKM and attitude scale. The result of model validation test obtained the following score: 4.0 (good) material validation 4.05 (good), item validation 4.03 (good), and lesson plan validation 4.15 (good). The result of t-test of achievement test was 9,729 with the significance level of 0.00<0.05, so Ho was rejected, means that the average of pre-learning and pre-learning in experiment class was not same. Meaning that there was significant effect on the model developed based on the controversial issues to improve student’s historical thinking.